Electrochemical Evaluation and Phase-related Impedance Studies on Silicon–Few Layer Graphene (FLG) Composite Electrode Systems - Qianye Huang (Nature Portfolio, 2018)
Abstract Silicon-Few Layer Graphene (Si-FLG) composite electrodes are investigated using a scalable electrode manufacturing method. A comprehensive study on the electrochemical performance and the impedance response is measured using electrochemical impedance spectroscopy. The study demonstrates that the incorporation of few-layer graphene (FLG) results in significant improvement in terms of cyclability, electrode resistance and diffusion properties. Additionally, the diffusion impedance responses that occur during the phase changes in silicon is elucidated through Staircase Potentio Electrochemical Impedance Spectroscopy (SPEIS): a more comprehensive and straightforward approach than previous state-of-charge based diffusion studies.